Tapa Malenggang: Politik Memori dan Transformasi Memori Kolektif di Kabupaten Batanghari - Puteri Soraya Mansur (Titian: Jurnal Ilmu Humaniora, 2022)
Collective memory is created by humans to perpetuate memories of past events. Individual memories influence the collective memories of society. Tapa Malenggang is one of the collective memories formed by the community in Batanghari Regency, Jambi Province. The purpose of this study is to explore the politics of memory and the transformation of collective memory from Tapa Malenggang. The method used in this research is the historical method which consists of four steps, namely heuristics, verification, interpretation, and historiography. The results of this study are Tapa Malenggang as a political representation of memory formed by the community and leaders so that it creates the transformation from a fish into a fairy tale, a monument, and a festival. Keywords: tapa malenggang, memory politics, collective memory, fairy tales.